The Role of Beneficial Microbiota in COVID-19: Insights from Key Bacterial Genera - Pabulo Henrique Rampelotto; Clarissa Reginato Taufer; Juliana da Silva (Microorganisms)
The COVID-19 pandemic has highlighted the need for a comprehensive understanding of the factors influencing disease severity and progression. Emerging research indicates that the human microbiota, particularly beneficial bacteria, significantly impacts immune responses and health outcomes in COVID-19 patients. While existing studies provide general insights into the relationship between the microbiota and probiotics with COVID-19, they often lack a detailed exploration of how specific bacterial taxa might be used as adjunctive treatments. This review aims to address this gap by focusing on ten key genera of beneficial bacteria, discussing their roles in COVID-19 and evaluating their potential as probiotics for prevention and treatment. The review covers the impact of these microbes on human health, their population alterations in COVID-19 patients, and their interactions with other viral infections. Among these microbes, several exhibit distinct patterns of abundance in COVID-19 patients, influencing disease outcomes and highlighting their potential roles in infection dynamics. In COVID-19 patients, populations of Akkermansia, Ruminococcus, and Roseburia are consistently reduced, while those of Faecalibacterium show a significant decline in more severe cases. Bacteroides presents varying effects depending on the species involved. Alterations in the abundance of Blautia and Lachnospiraceae are associated with increased inflammation and disease severity. Likewise, the depletion of Lachnospira and Coprococcus populations, both linked to anti-inflammatory effects, may exacerbate symptom severity. Oscillospira, though less studied, is connected to overall health and could have implications for viral infections. This review synthesizes the current understanding of these beneficial microbes to highlight the importance of maintaining a healthy microbiota to alleviate the impact of COVID-19 and contribute to the development of novel therapeutic strategies involving microbiota modulation.